PENDIDIKAN KARAKTER PADA GERAKAN KELAS INSPIRASI - Diamah Fitriyyah (Jurnal keilmuan dan Kependidikan dasar, 2023)
This research is motivated by the condition of students in choosing professional ideals. They have minimal description of the various professions, the more science and technology develops, the more types of work and professions develop. Through this Serang Inspiration Class (KI) movement, students will see first-hand various interesting professions to aspire to. Character education in the 2019 Serang Inspiration Class movement is a qualitative field of research. This study describes, identifies, and qualitatively analyzes character education in the 2019 Serang Inspiration Class movement activities. The 2019 Serang Inspiration Class movement is a movement in the world of education with the concept of introducing various professions by presenting these professional figures directly in front of students. elementary level. The subjects in the study were 10 elementary schools in the Anyar sub-district, Serang district, which were the targets of the 2019 Serang KI after going through the survey stage by committee volunteers. There are about 220 volunteers who work directly with various professions. The object of this research is the inspirational class movement and character education. Then the main instrument in this study was the direct researcher involved in the activity as the organizing committee. While the analysis technique uses the Miles and Huberman model. The character education values ​​that emerged in the implementation of KI Serang 2019 were 98 divided into 5 domains, namely: 1) Characters related to God (religious), 2) Characters related to oneself (honest, disciplined, hard-working, creative, independent, curiosity, fond of reading, responsibility), 3) Characters related to fellow human beings (tolerance, democratic, peace-loving, friendly/communicative, appreciating achievement), 4) Characters related to nationality (love for the motherland), 5) Character related to the environment (environmental care, social care).